THE DEVELOPMENT AND MODERNIZATION OF THE FERGANA REGIONAL MUSEUM OF HISTORY AND CULTURE IN THE YEARS OF INDEPENDENCE - Alisher Ahmadjonovich Aloxunov (Western European Studies, 2025)
This article is dedicated to the history, material and technical condition, and activities of the Fergana Regional History and Culture State Museum. It discusses the renewal of the museum during the years of independence, the strengthening of its material and technical base, its regulations, the activities of its existing branches, and the implementation of modern technologies. Proposals are presented regarding the development of the Fergana Museum based on new concepts, the enhancement of its tourism potential, and the preservation of cultural heritage
Keywords: Fergana history; cultural heritage; museum